CAMP@FLASH: an end‐station for imaging, electron‐ and ion‐spectroscopy, and pump–probe experiments at the FLASH free‐electron laser. (2nd August 2018) - Erk, Benjamin; Müller, Jan P.; Bomme, Cédric; Boll, Rebecca; Brenner, Günter; Chapman, Henry N.; Correa, Jonathan; Düsterer, Stefan; Dziarzhytski, Siarhei; Eisebitt, Stefan; Graafsma, Heinz; Grunewald, Sören; et al.
Abstract : Beamline BL1 at the FLASH free‐electron laser facility at DESY was upgraded with new transport and focusing optics for the installation of the new permanent CAMP end‐station, a multi‐purpose instrument optimized for electron‐ and ion‐spectroscopy, imaging and pump–probe experiments. An overview of the layout, beam transport, focusing capabilities, and experimental possibilities of this new end‐station, as well as results from its commissioning and first experiments, are presented. Abstract : The non‐monochromatic beamline BL1 at the FLASH free‐electron laser facility at DESY was upgraded with new transport and focusing optics, and a new permanent end‐station, CAMP, was installed. This multi‐purpose instrument is optimized for electron‐ and ion‐spectroscopy, imaging and pump–probe experiments at free‐electron lasers. It can be equipped with various electron‐ and ion‐spectrometers, along with large‐area single‐photon‐counting pnCCD X‐ray detectors, thus enabling a wide range of experiments from atomic, molecular, and cluster physics to material and energy science, chemistry and biology. Here, an overview of the layout, the beam transport and focusing capabilities, and the experimental possibilities of this new end‐station are presented, as well as results from its commissioning.